Pro SQL Server on Linux : including container-based deployment with Docker and Kubernetes - Ward, Bob (Computer engineer) (Apress, 2018)
Get SQL server up and running on the Linux operating system and containers. No database professional managing or developing SQL server on Linux will want to be without this deep and authoritative guide by one of the most respected experts on SQL server in the industry. Get an inside look at how SQL server for Linux works through the eyes of an engineer on the team that made it possible. Microsoft SQL Server is one of the leading database platforms in the industry, and SQL Server 2017 offers developers and administrators the ability to run a database management system on Linux, offering proven support for enterprise-level features and without onerous licensing terms. Organizations invested in Microsoft and open source technologies are now able to run a unified database platform across all their operating system investments. Organizations are further able to take full advantage of containerization through popular platforms such as Docker and Kubernetes. "Pro SQL Server on Linux" walks you through installing and configuring SQL Server on the Linux platform. The author is one of the principal architects of SQL Server for Linux, and brings a corresponding depth of knowledge that no database professional or developer on Linux will want to be without. The book covers day-to-day management and troubleshooting, including diagnostics and monitoring, the use of containers to manage deployments, and the use of self-tuning and the in-memory capabilities. Also covered are performance capabilities, high availability, and disaster recovery along with security and encryption. The book covers the product-specific knowledge to bring SQL Server and its powerful features to life on the Linux platform, including coverage of containerization through Docker and Kubernetes. What you'll learn: Install and configure Microsoft's flagship database product on the Linux platform ; Manage your deployments using container technology through Docker and Kubernetes ; Know the basics of building databases, the T-SQL language, and developing applications against SQL Server on Linux ; Use tools and features to diagnose, manage, and monitor SQL Server on Linux ; Scale your application by learning the performance capabilities of SQL Server ; Deliver high availability and disaster recovery to ensure business continuity ; Secure your database from attack, and protect sensitive data through encryption ; Take advantage of powerful features such as Failover Clusters, Availability Groups, In-Memory Support, and SQL Server's Self-Tuning Engine ; Build and maintain schemas and perform management tasks from both GUI and command line